2010
DOI: 10.1088/1742-6596/234/2/022034
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical approach to find current distribution and AC losses in coaxial assembly of twisted HTS tapes in single layer arrangement

Abstract: A new numerical approach to find current distribution and AC losses in coaxial assembly of twisted HTS tapes in single layer arrangement Abstract. This paper presents a novel technique for evaluating AC losses and current distribution in single layer assemblies of coaxially wound thin conductors, such as YBCO coated conductors. The proposed approach takes into account the twisted geometry of the individual superconducting tapes by considering the integral relation between the magnetic vector potential and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Although this model represents a 3D structure, it does not account for the finite thickness of the conductors. Infinitesimally thin approximations have already been used in several instances for 2D and 3D models [8][9][10]. In essence, they do not account for current distributions across the tape's thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Although this model represents a 3D structure, it does not account for the finite thickness of the conductors. Infinitesimally thin approximations have already been used in several instances for 2D and 3D models [8][9][10]. In essence, they do not account for current distributions across the tape's thickness.…”
Section: Introductionmentioning
confidence: 99%
“…According to the left-hand side of figure 4, as was already known [7,8], with the typical design the AC losses decrease as the size of the gap decreases. In this figure, it is observed that, for a given gap, the AC losses remain the same regardless of the winding angle of the cable.…”
Section: Cyclic Overlapped Designmentioning
confidence: 72%
“…As explained, the edge losses arise from the presence of small gaps between the adjacent tapes (shown in figure 2). Therefore, the minimum AC losses with a typical design of single layer HTS cables are achieved when these gaps are completely closed [7,8]. But due to mechanical considerations, there is a minimum size for the gap (0.6-0.8 mm) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the experimental setup for superconducting cables is very costly and time-consuming. Therefore, using the finite-element method (FEM) in the simulation of AC loss of superconducting power transmission cables, instead of experimental work, has been preferred by many researchers [6][7][8][9][10]. Simulations of cables have also been useful for predicting and understanding the measured loss mechanism for either transport or magnetization loss [11,12].…”
Section: Introductionmentioning
confidence: 99%